Prevalence, predictors, and management for balloon uncrossable or undilatable lesions in patients undergoing percutaneous coronary intervention with in-stent restenosis chronic total occlusion - Wang, Yong; Hou, Ai-jie; Luan, Bo; Zhang, Xiao-jiao; Li, Zhao-yu; Pei, Xiao-yang (Frontiers in Cardiovascular Medicine, 2023)
Background Percutaneous coronary intervention for in-stent restenosis (ISR) chronic total occlusion (CTO) has been a great challenge. There are occasions when the balloon is uncrossable or undilatable (BUs) even though the guidewire has passed, leading to failure of the procedure. Few studies have focused on the incidence, predictors, and management of BUs during ISR-CTO intervention. Methods Patients with ISR-CTO were recruited consecutively between January 2017 and January 2022 and divided into two groups based on the presence of BUs. The clinical data of the two groups (BUs group and non-BUs group) were retrospectively analyzed and compared to explore the predictors and clinical management strategies of BUs. Results A total of 218 patients with ISR-CTO were included in this study, 23.9% (52/218) of whom had BUs. The percentage of ostial stents, stent length, CTO length, the presence of proximal cap ambiguity, moderate to severe calcification, moderate to severe tortuosity, and J-CTO score were higher in the BUs group than in the non-BUs group (p < 0.05). The technical success rate and the procedural success rate were lower in the BUs group than in the non-BUs group (p < 0.05). Multivariable logistic regression analysis showed that ostial stents (OR: 2.011, 95% CI: 1.112–3.921, p = 0.031), the presence of moderate to severe calcification (OR: 3.383, 95% CI: 1.628–5.921, p = 0.024) and moderate to severe tortuosity (OR: 4.816, 95% CI: 2.038–7.772, p = 0.033) were independent predictors of BUs. Conclusion The initial rate of BUs in ISR-CTO was 23.9%. Ostial stents, presence of moderate to severe calcification, and moderate to severe tortuosity were independent predictors of BUs.